Dark matter heats up in dwarf galaxies. Issue 1 (3rd January 2019) - Read, J I; Walker, M G; Steger, P
ABSTRACT: Gravitational potential fluctuations driven by bursty star formation can kinematically 'heat up' dark matter at the centres of dwarf galaxies. A key prediction of such models is that, at a fixed dark matter halo mass, dwarfs with a higher stellar mass will have a lower central dark matter density. We use stellar kinematics and HI gas rotation curves to infer the inner dark matter densities of eight dwarf spheroidal and eight dwarf irregular galaxies with a wide range of star formation histories. For all galaxies, we estimate the dark matter density at a common radius of 150 pc, ρ _DM(150 pc) . We find that our sample of dwarfs falls into two distinct classes. Those that stopped forming stars over 6 Gyr ago favour central densities ρ _DM(150 pc)10^8 M⊙ kpc −3, consistent with cold dark matter cusps, while those with more extended star formation favour ρ _DM(150 pc)10^8 M⊙ kpc −3, consistent with shallower dark matter cores. Using abundance matching to infer pre-infall halo masses, M 200, we show that this dichotomy is in excellent agreement with models in which dark matter is heated up by bursty star formation. In particular, we find that ρ _DM(150 pc) steadily decreases with increasing stellar mass-to-halo mass ratio, M * / M 200 . Our results suggest that, to leading order, dark matter is a cold, collisionless, fluid that can be kinematically 'heated up' and moved around.